Comparison of postharvest commercial products in two varieties of spray chrysanthemum on the Bogota Plateau - Liliana R. Hidalgo P. (Agronomía Colombiana, 2012)
The ornamental quality of chrysanthemum (Dendranthema grandiflorum (Ramat.) Kitamura) is affected by postharvest premature senescence of foliage. The longevity of the flower stem is limited by yellowing of the foliage while the flower itself maintains ornamental value. The objective of this research was to compare the efficiency of anti-senescence and hydrating commercial products used in postharvest handling of the chrysanthemum varieties Polaris and Yellow Polaris. The variables floral longevity, relative water content (RWC) and chlorophyll content were measure. Flowering spray chrysanthemum stems underwent vase life evaluation for 10 days. In the beginning, there were differences between treatments in the content of chlorophyll; however, the onset of premature senescence symptoms on the foliage can be delayed through the application of treatment RVB clear (hydrating and bactericide, it’s contains a complex of biocide, organic acidifying and surfactant) in a hydration solution or in a mixture with the SVB treatment (foliar anti-senescence based on hormones). We determined a total chlorophyll content of 0.011 mg g-1 of leaf fresh weight as a threshold, above which no symptoms of yellowing foliage are visible in spray chrysanthemum. For the variable RWC, a differential effect of the treatments was not seen for the tested varieties. There was also no correlation between hydration status and chlorophyll content in the foliage.